Aging, rejuvenation, and memory phenomena in a lead-based relaxor ferroelectric - Böhmer, Roland; Kircher, O. (Springer, 2002)
Isothermal aging and temperature cycle experiments were done on the relaxor ferroelectric lead magnesium niobate mixed with 10% lead titanate (PMN-10PT) around and below the diffuse maximum of the dielectric loss. With increasing aging time tw the isothermal evolution of the linear susceptibility follows a power law and does not show frequency scaling. The non-linear susceptibility, however, obeys nearly perfect ωt w-scaling. After aging the sample at a single temperature we observed both rejuvenation and memory effects in temperature cycle experiments. This observation indicates symmetric behavior in the sense that it shows up irrespective of whether cooling with subsequent re-heating or heating with subsequent re-cooling was performed. The memory effect is absent if subsequent to aging the temperature is increased significantly above that corresponding to the maximum in the dielectric loss. The symmetric behavior within negative and positive temperature cycles under these conditions can be rationalized by the notion of movable domain walls. These become fixed in their configuration on a large spatial scale while more flexible wall segments still show re-conformation processes when cooling or heating the sample after aging.
Keywords: 530